Optimizing Doppler Ultrasound Parameters: The Study of Insonation Angle, PRF, and Dynamic Range in Blood Flow Assessment - Oktamuliani, Sri; Ishii, Takuro; Saijo, Yoshifumi (Jurusan Fisika FMIPA Universitas Andalas, 2025)
Doppler ultrasound is critical in medical diagnostics for evaluating blood flow and detecting vascular conditions. Accurate blood flow velocity measurements depend on insonation angle, Pulse Repetition Frequency (PRF), and dynamic range. This study optimizes these parameters to enhance Doppler ultrasound performance and diagnostic accuracy. A Xario-100 ultrasound machine and the Doppler 403TM flow phantom were used to evaluate the effects of insonation angle, PRF, and dynamic range on measurement accuracy. Insonation angles of 0o and 60o were tested to assess their impact on aliasing and precision. At 0o, significant aliasing occurred, while 90o, aliasing was minimized. PRF settings were adjusted from 14,000 Hz to 17,900 Hz, with higher PRF extending the Nyquist Velocity from 9.8 cm/s to 37.4 cm/s, reducing aliasing and improving high-flow measurement clarity in the dynamic range from 30 dB to 60 dB, with optimal contrast observed at 50 dB. Histogram analysis revealed a balanced pixel intensity distribution at 50 dB, enhancing the Signal-to-Noise Ratio (SNR). The findings demonstrate an insonation angle of 60o, at PRF 17,900 Hz, and a dynamic range of 50 dB optimal Doppler ultrasound performance. Standardizing these parameters can improve diagnostic accuracy, supporting better patient outcomes in clinical practice.